The transformation of a man's heart - Smith, Stephen W., 1954- (Downers Grove, Ill. : IVP Books, 2006)
This book is a book of stories: twelve men write from their hearts about their own journey toward transformation. Gary Chapman, author of The Five Love Languages, shares his journey toward experiencing a transformed marriage with his wife. Ross Campbell, Christian psychiatrist and author of How to Really Love Your Child, discusses his heart's transformation in growing as a father with his children. Gordon Dalbey pioneered the men's movement in his Healing the Masculine Soul. Here he shares how our past must be transformed in order to experience all God has for us as men. James Houston, mentor and friend to many Christian leaders throughout the world, considers how his own journey toward transformation reflects the call God places on every man's heart. These and other leading men in their fields come alongside you in The Transformation of a Man's Heart, telling you their stories and pointing you toward the God who in the beginning wrote every man a happy ending. This book is full of stories. Some will make you think. Others will make you cry. Still others will make you kneel. All will make you want to be a better man.
Foreword / Ken Gire -- Transformation : understanding the process / Stephen W. Smith -- The spiritual journey : embracing transformation / Howard Baker -- Inward -- Intimacy with God : growing through the years / Doug Stewart -- The past : healing from the wounds / Gordon Dalbey -- Failure : exploring the benefits / Bob Fryling -- Vocation : listening for the voice that calls us / Fil Anderson -- Outward -- Friendships : experiencing others on the journey / David Benner -- Sex : learning to tell our sexual story / John Pierce -- Marriage : loving the heart of a woman / Gary Chapman -- Parenting : being like Jesus to our children / D. Ross Campbell -- Forward -- Legacy : investing in the future / Craig Glass -- Transformation across the lifespan : one man's journey / James Houston.
Includes bibliographical references (pages 189-191).
Keywords: Christian life